Preserved Intention Maintenance and Impaired Execution of Prospective Memory Responses in Schizophrenia: Evidence from an Event-based Prospective Memory Study - Demeter, Gyula; Szendi, István; Domján, Nóra; Juhász, Marianna; Greminger, Nóra; Szőllősi, Ágnes; Racsmány, Mihály (Frontiers in Psychology, 2016)
Executive system dysfunction and impaired prospective memory (PM) are widely documented in schizophrenia. However, it is not yet clarified which components of PM function are impaired in this disorder. Two plausible target components are the maintenance of delayed intentions and the execution of PM responses. Furthermore, it is debated whether the impaired performance on frequently used executive tasks is associated with deficit in PM functions. The aim of our study was twofold. First, we aimed to investigate the specific processes involved in event-based PM function, mainly focusing on difference between maintenance of intention and execution of PM responses. Second, we aimed to unfold the possible connections between executive functions, clinical symptoms, and PM performance. An event-based PM paradigm was applied with three main conditions: baseline (with no expectation of PM stimuli, and without PM stimuli), expectation condition (participants were told that PM stimuli might occur, though none actually did), and execution condition (participants were told that PM stimuli might occur, and PM stimuli did occur). This procedure allowed us to separately investigate performances associated with intention maintenance and execution of PM responses. We assessed working memory and set-shifting executive functions by memory span tasks and by the Wisconsin Card Sorting Test (WCST), respectively. Twenty patients diagnosed with schizophrenia and 20 healthy control subjects (matched according to age and education) took part in the study. It was hypothesized that patients would manifest different levels of performance in the expectation and execution conditions of the PM task. Our results confirmed that the difference between baseline performance and performance in the execution condition (execution cost) was significantly larger for participants diagnosed with schizophrenia in comparison with matched healthy control group. However, this difference was not observed in the expectation condition. The PM performance in the execution condition was correlated with impaired executive functions in schizophrenia. Specifically, the size of execution cost positively correlated with percent of perseverative errors committed on WCST by the patient group. Our results suggest that maintenance of delayed intentions is unimpaired in schizophrenia, whereas the impairment in execution of PM responses is associated with set-shifting deficit.